Green Purchase Intention: Analisis Green Perceived Value Dan Green Brand Image Pada Generasi Z - Erik Erik; Salsabila Rizky Andriyani; Fildzah Rudyah Putri Harahap (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
This study investigates the impact of green perceived value and green brand image on green purchase intention of electric motorcycles among Generation Z consumers. Employing a quantitative approach, data were collected through online questionnaires distributed via Google Forms, using convenience sampling. A total of 303 respondents from Generation Z who hold a motorcycle driving license (SIM C) participated. Measurement instruments included green purchase intention (Chen & Chang, 2012), green perceived value (Woo & Kim, 2019), and green brand image (Chen, 2010). Multiple linear regression analysis was conducted using IBM SPSS version 26. The results reveal that both green perceived value and green brand image significantly influence green purchase intention, jointly explaining 32.6% of its variance. These findings underscore the importance of green perceived value and green brand image in shaping consumer green purchase intentions, particularly within Generation Z, offering valuable insights for marketers and policymakers aiming to promote sustainable mobility solutions. Keywords:Brand Image; Perception Value; Eco Friendly; Buying Intention